1998
DOI: 10.1097/00042560-199803010-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Dose Study to Assess the Penetration of Stavudine Into Human Cerebrospinal Fluid in Adults

Abstract: Penetration of stavudine into the cerebrospinal fluid (CSF) was studied in healthy humans. In this open, randomized study, a single oral dose of 40 mg of stavudine was given to 12 fasting volunteers > or = 18 years of age. Subjects were divided into three groups based on the time of CSF sampling (i.e., 0.75-1.25, 2-3, or 4-5 hours after dosing). Blood samples were collected over an 8-hour period after dosing and included a sample simultaneous with CSF collection to permit an estimate of CSF : plasma ratios. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…CART consisted of treatment with PMPA and RCV (75,76). PMPA is a nucleotide analog that does not penetrate the CNS, and RCV is a nucleoside analog of a class that has low-to-nondetectable CNS penetration (40,(77)(78)(79). PMPA and RCV were dissolved in water at 30 mg/ml and the PMPA pH adjusted to 7.0 with 3 N NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…CART consisted of treatment with PMPA and RCV (75,76). PMPA is a nucleotide analog that does not penetrate the CNS, and RCV is a nucleoside analog of a class that has low-to-nondetectable CNS penetration (40,(77)(78)(79). PMPA and RCV were dissolved in water at 30 mg/ml and the PMPA pH adjusted to 7.0 with 3 N NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…This type of model is justified for two reasons. First, there is evidence that drug concentrations, and therefore efficacies, are reduced in certain physiologically distinct sites in the body such as the testes and the brain (Lewis et al, 1996;Haworth et al, 1998;Schlegel and Chang, 1998). Second, in vitro studies have demonstrated that there can be heterogeneities in intracellular drug concentrations.…”
Section: Compartmental Models With a Robust Low Steady State Viral Loadmentioning
confidence: 99%
“…3 indicates that the concentration of virus in the main compartment is lower than that in the drug sanctuary due to the less efficacy in the latter. This may explain why there is less effect of treatment on some physiological sites such as the brain [6,12].…”
Section: Global Stability Of Equilibria E 0 and Ementioning
confidence: 99%
“…Examination of changes in drug efficacy after a treatment with antiretroviral drugs has shown that drug efficiencies are reduced in certain physiologically distinct sites such as the tests [2,18] and the brain [18,6,12]. Researches in vitro [2,16,17,10] have indicated that drug efficacy may vary in different types of cells.…”
Section: Introductionmentioning
confidence: 99%